Collective Epithelial Cell Sheet Adhesion and Migration on Polyelectrolyte Multilayers with Uniform and Gradients of Compliance - Martinez, Jessica S. (Exp Cell Res, 2016)
Polyelectrolyte multilayers (PEMUs) are tunable thin films that could serve as coatings for biomedical implants. PEMUs built layer by layer with the polyanion poly(acrylic acid) (PAA) modified with a photosensitive 4-(2-hydroxyethoxy) benzophenone (PAABp) group and the polycation poly(allylamine hydrochloride) (PAH) are mechanically tunable by UV irradiation, which forms covalent bonds between the layers and increases PEMU stiffness. PAH-terminated PEMUs (PAH-PEMUs) that were uncrosslinked, UV-crosslinked to a uniform stiffness, or UV-crosslinked with an edge mask or through a neutral density optical gradient filter to form continuous compliance gradients were used to investigate how differences in PEMU stiffness affect the adhesion and migration of epithelial cell sheets from scales of the fish Poecilia sphenops (Black Molly) and Carassius auratus (Comet Goldfish). During the progressive collective cell migration, the edge cells (also known as ‘leader’ cells) in the sheets on softer uncrosslinked PEMUs and less crosslinked regions of the gradient formed more actin filaments and vinculin-containing adherens junctions and focal adhesions than formed in the sheet cells on stiffer PEMUs or glass. During sheet migration, the ratio of edge cell to internal cell (also known as ‘follower’ cells) motilities were greater on the softer PEMUs than on the stiffer PEMUs or glass, causing tension to develop across the sheet and periods of retraction, during which the edge cells lost adhesion to the substrate and regions of the sheet retracted toward the more adherent internal cell region. These retraction events were inhibited by the myosin II inhibitor Blebbistatin, which reduced the motility velocity ratios to those for sheets on the stiffer PEMUs. Blebbistatin also caused disassembly of actin filaments, reorganization of focal adhesions, increased cell spreading at the leading edge, as well as loss of edge cell-cell connections in epithelial cell sheets on all surfaces. Interestingly, cells throughout the interior region of the sheets on uncrosslinked PEMUs retained their actin and vinculin organization at adherens junctions after treatment with Blebbistatin. Like Blebbistatin, a Rho-kinase (ROCK) inhibitor, Y27632, promoted loss of cell-cell connections between edge cells, whereas a Rac1 inhibitor, NSC23766, primarily altered the lamellipodial protrusion in edge cells. Compliance gradient PAH-PEMUs promoted durotaxis of the cell sheets but not of individual keratocytes, demonstrating durotaxis, like plithotaxis, is an emergent property of cell sheet organization.